Indoleamine-2,3-Dioxygenase Mediates Emotional Deficits by the Kynurenine/Tryptophan Pathway in the Ethanol Addiction/Withdrawal Mouse Model - Jiang, Xi; Lin, Qian; Xu, Lexing; Chen, Ziwei; Yan, Qizhi; Chen, Lei; Yu, Xuefeng (Frontiers in Cellular Neuroscience, 2020)
Objective: Our study was designed to investigate whether indoleamine-2,3-dioxygenase (IDO)-mediated kynurenine/tryptophan (KYN/TRP) pathway participates in the development of emotional deficits of ethanol addiction/withdrawal mice. Methods: Expression of proinflammatory factors including tumor necrosis factor α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) were tested by enzyme linked immunosorbent assay (ELISA). The IDO levels in the hippocampus, cerebral cortex and amygdala were measured by polymerase chain reaction (PCR) and western blot, and the neurotransmitters were tested by high performance liquid chromatography (HPLC). Emotional deficits of mice were evaluated by behavioral tests. Results: Expression levels of inflammatory factors (TNF-α, IL-1β and IL-6) were increased in mice after 4 weeks of alcohol exposure. As for indoleamine 2,3-dioxygenase (IDO) expression, only the subtype IDO1 was found to increase at both mRNA level and protein level in all the tested brain regions of ethanol addiction/ withdrawal mice. In behavioral tests, mice exposed to alcohol showed the gradually-declined memory function, accompanied by anxiety-like and depressive-like behaviors. Meanwhile, increased expression of KYN, decreased expression of 5-HT and abnormal expression of 3-HK and KA were found in the hippocampus, cerebral cortex and amygdala of ethanol addiction/withdrawal mice. Interestingly, the IDO1 inhibitor, 1-methyl-L-tryptophan (1-MT), reversed all above alterations induced by ethanol in mice. Conclusion: Our results suggested that TRP/KYN pathway, medicated by IDO1, in the hippocampus, cerebral cortex and amygdala, plays an important role in the development of emotional deficits caused by ethanol addiction and withdrawal.